An integrated photovoltaic/wind/biomass and hybrid energy storage systems towards 100% renewable energy microgrids in university campuses - Al-Ghussain, Loiy; Darwish Ahmad, Adnan; Abubaker, Ahmad M.; Mohamed, Mohamed A. (Sustainable energy technologies and assessments, 2021)
•Hybrid solar/wind-biomass system showed high synergetic performance.•Utilizing biomass to supply the baseload increased demand-met by the hybrid system.•An integrated hybrid energy storage increased the system’s autonomy significantly.•Achieving carbon–neutral campuses smoothens countrys’ transition to 100% renewables.•The proposed system is feasible and can meet close to 100% of the energy demand. The incorporation of energy storing units into hybrid systems reallocates the excess electricity to meet demand requirements in the deficiency periods. This study seeks to determine the optimal size of a Photovoltaic (PV)/wind/biomass hybrid system with and without energy storage built on the base of boosting the demand–supply fraction (DSF) and the renewable energy fraction (FR) with a net present value larger than or equals to zero. The Generalized Reduced Gradient algorithm has been utilized in this study to evaluate the optimal components’ capacities of the proposed system. Middle East Technical University Northern Cyprus Campus was used as a case study. The proposed system consists of 1.79 MW PV, 2 MW wind and 0.92 MW biomass systems with 24.39 MWh pumped hydro storage system and 148.64 kWh batteries achieving FR of 99.59%, DSF of 98.86%, and a cost of electricity equals to 0.1626 $/kWh. The simulations results proved that the integration of a hybrid energy storage system with the PV/wind/biomass system ensures very high autonomy approaching almost 99%. Finally, considering the significant excess energy produced by the tri-hybrid system, this excess could also be allocated towards meeting the campus’s thermal and domestic hot water demands creating a polygeneration power system.